Rice diversity and the joy of eid - Akhter, F.; Khatun, A.; Khatun, F.; Islam, R.; Mostafa, G.; Vernooy, Ronnie (2019)
This brief presents the results of research on the conservation and sustainable use of rice diversity in Bangladesh and how the rice varieties used and planted are intrinsically linked to religious festivals, food culture, land morphology and the climate that shape rice farming/cropping in this region. It highlights the important roles played by Community Seed Wealth Centers (community seed banks) and the Nayakrishi farmers, who manage them, in ensuring the conservation of rice varieties that are in danger of disappearing, and in supplying farmers with diverse, good quality seed. It also demonstrates the key roles played by women farmers as seed custodians and the strategic research and capacity building activities carried out by the Community Seed Wealth Centers.